Suppression of superconductor quasiparticle tunneling into single-walled carbon nanotubes - Krstic, Vojislav; Roth, Siegmar; Burghard, Marko; Weis, Jürgen; Kern, Klaus (Physical Review B, 2003)
Electrical transport through single-walled carbon nanotubes with weak electrical coupling to superconducting leads has been studied theoretically and experimentally. A simple model is considered to describe single-particle tunneling into a Luttinger-liquid-like state from electrically weak connected superconducting electrodes. This involves the superconductor’s quasiparticle and the Luttinger liquid’s excitation density of states. Experimentally, the suppression of quasiparticle tunneling induced current peaks was observed at temperatures below 0.1 K, which we attributed to the Luttinger-liquid-like excitation spectrum of the single-walled carbon nanotube.